Keynote Address Southeast Asia: Imperial Themes - Wang , Gungwu (Penerbit Universiti Sains Malaysia (USM Press), 2017)
A celebratory conference of this kind should allow the keynote lecture to be somewhat more personal than normal. It is with that in mind that I have linked the theme, 'Southeast Asia: Past, Present and Future', to the person whose birthday we are celebrating. I do not know if I can do that successfully but will try by pursuing some of Nick's [Nicholas Tarling] and my own life and professional experiences with imperial themes in Southeast Asian history. Why 'imperial themes'? Would not that be too much of a bias towards the past? It would seem to ignore the conference theme to include both the present and the future. Of course, I have an historian's weakness for what is past; in this case, even 'privileging' a past paradigm that Southeast Asians today might prefer to forget. My excuse is that the party is for Nick, who is even more the historian than I am, and this is a rare opportunity for me to connect with him in the Southeast Asian context. But I shall not only talk about the past. I also hope to show that there are imperial themes in diﬀerent contexts and diﬀerent kinds of empires. Many of us wish to see the end of empires forever, and indeed some kinds of empires may have come to an end. But imperial themes are pervasive and resilient and may be more present than we think, and more relevant for the future than we would want. I recall suggesting a few months ago, when commemorating the end of the Second World War in Asia, that the kind of empire that the Japanese had tried to establish in Southeast Asia between 1941 and 1945 was gone and never to return.